New evidence on the determinants of the gap between child support awards and child support receipts (Economia Aplicada, 2007)
Social scientists and policymakers have documented dramatic changes in the structure of US families over the past decades. In this paper, I analyze the child support compliance gap- the difference between expected payments and received child support payments- using a unique data set from the 1990-1993 SIPP on child support agreements. I explore the factors that determine the existence and the magnitude of a gap in payments using a probit model and regression analysis. Results suggest that both the existence of and magnitude of the child support gap are positively influenced by non-voluntary agreements received by the custodial parent.